The holy fool : Christian faith and theology in J.M.R. Lenz - Pope, Timothy F. (Timothy Fairfax), 1947- (McGill-Queen's University Press, 2003)
J.M.R. Lenz is remembered as the most creative and original of Goethe's Strasbourg friends and, because of failures in his personal life, as a figure of pathos. The son of a Lutheran pastor who received a theological education at the university of Koenigsberg, Lenz was a religious thinker who saw himself as prophet as well as poet. Timothy Pope's The Holy Fool is the first study of Lenz to consider how Christian faith shaped his literary theory and practice and was responsible for his unwise expectations about the increasingly secular world for which he wrote.